Aquatic habitats (Assignment Discovery (Television program), 1997)
Describes what grows and flourishes in four different aquatic habitats and how microclimates determine an animal's biological destiny. The habitats include: the ocean habitat of sharks; the Scottish lake of Loch Ness; the mangrove swamps of the Florida Everglades; and the estuaries of Chesapeake Bay.